TOPENG BABAKAN - Toto Sudarto (Greget, 2009)
Throughout the course of its journey, topeng babakan Cirebon has become a milestone, which has coloured the course of the history of dance in West Java. This research discovers the changes and developments in topeng babakan from 1900 to 1990. The study of the subject of this tesis uses a historical approach, with the aid of social and cultural studies. Topeng Babakan is a performing folk art, the performance of which is still related to traditional ceremony such as ngunjung, mapag sri, ngarot, and so on. It spread through West Java, begining as a a traveling show or bebarang (troupe of performing beggars) at the start of the 20th century. This drew the attention of the aristocrats or menak, to learn the art of Cirebon masked theater. In it subsequent development, this dance greatly infuenced other dance forms in the Priangan region and in West Java in general. The rise and fall of topeng babakan performance activities was largely infuenced by developments in siciety, ehich constantly changed with the developments of the age, and developments in information technology and communication.Keyword : topeng babakan, bebarang, changes, and developments